Conhecimento ecológico de populações indígenas e tradicionais sobre animais silvestres e uso de barreiros na Amazônia - Pereira, Franciany Gabriella Braga (2022)
Effective estimation of wildlife population abundance is an important component of population monitoring, and ultimately essential for the development of conservation actions. As the conservation research community faces the need to standardise effective methods for estimating fauna abundance, in chapter 2 of this thesis, we compared concomitant abundance data for 91 wild species from diurnal line transects (9,221 km of trails) and a LEK-based method (291 structured interviews) at 18 sites in Central and Western Amazonia. We found a significant agreement of population abundance indices for diurnal and game species. This relationship was also positive regardless of species sociality, body size and locomotion mode; and of sampled forest type (upland and flooded forests). However, line transects were not effective at surveying many species occurring in the area, with 40.2% and 39.8% of all species being rarely and never detected in at least one of the survey sites. On the other hand, these species were widely reported by local informants to occur at intermediate to high abundances. We demonstrate the effectiveness of interviews for abundance estimation. However, we still needed to know who should be interviewed in abundance estimation studies and about which species we could ask. For this, in chapter 3, we analysed the degree of consensus about the abundance of 95 species among 333 people with different social and wildlife experiences characteristics in 20 demographically distinct sites in the Western and Central Amazon. We found that village consensus was significantly higher the lower the population size of a given village. However, a high score of consensus (>0.6) was find regarding the species population abundance for all of the sampled villages and for 79.64% of the interviewees. The consensus value was also high regardless of the interviewees' hunting experience. Considering all 95 species, we found a high consensus score in all 20 sampled sites for 81 species (85.26%). Species that have greater consensus scores about their abundance are those living in larger sized groups, more abundant and more hunted. Specifically in relation to hunting, in some regions of Amazonia, 25% of the hunting activities occur in the salt licks, which consist in places with a higher concentration of natural minerals in the soil and which is Franciany G. Braga Pereira 16 often found on the edges of creeks, therefore they are liable to periodic flooding as the level of water rises. The hunters hang their nets above the salt licks and wait for game animals to visit to ingest the mineral-rich soil. In the Amazon rainforest, animals exhibit geophagical behaviour in salt licks to obtain key mineral supplementation and detoxicate from plant secondary compounds, reducing digestive disorders in their bodies. In a place visited by so many wild species, during the long period that hunters spend there waiting for the target species, hunter can also acquire a high level of knowledge about species that pass-through salt licks during the year. Through LEK- based methods, in chapter 4, we obtained information on 31 species of vertebrates visiting 56 salt licks in two regions of Central Amazon through different seasons. In terms of types of salt licks, we found three distinct categories (barreiro, chupador and canamã) depending on the salt lick size, animals’ visit period, and the diversity of visitors, as well as by the flooding period of the creeks water. Despite soil and water consumption in salt licks being the main attraction of wild species visiting these sites, species identified from the interviews as users of the salt licks also visit the place for bathing, predation and other ecological relationships and behaviours. In general, the season with the highest abundance of wild animals was the receding floodwaters season, because in this period the water level of creeks decreases and so the salt lick is exposed. In addition to natural salt licks, the higher concentration of minerals in Amazon soils has also been generated by the oil extraction industry, contaminating the soil with “produced waters”, the main by-product of this industry and which includes a high concentration of minerals. Additionally, oil-polluted soils also contain high concentrations of toxic petrogenic compounds. Through local ecological knowledge, oil-contaminated sites where wild animals consume the soil were identified in Western Amazon. In chapter 5, we investigated the geophagy of oil-polluted soil and water by 26 species of mammals and birds through the analysis of 8,623 videos recorded from a camera trap programme in three natural salt licks and sixteen oil-polluted salt licks located in an oil block concession in Amazon rainforest. We documented a total of 3,818 independent visits from 26 species, with 62.3% of these visits displaying soil ingestion Franciany G. Braga Pereira 17 proofs from 18 different species. Considering visits with soil ingestion, Tapirus terrestris accounted for 69,58% of the visits, followed by Mazama americana (13,75%). We did not find a significant difference in the visit frequency for natural salt licks when compared to oil-polluted salt licks, with the visitation rate high in both. Our results provide relevant data to confirm that geophagy by wildlife is not an unusual phenomenon in oil-polluted salt licks, but rather a widespread behaviour in oil extractive areas in the Amazon. Even worst, these compounds can bioaccumulate in animals’ tissues and some can even biomagnify through the food chain, including top predators and also local human populations (whose subsistence depends on wild meat). This makes the consumption of oil-polluted soil a major concern for conservation biodiversity and public health.